2010
DOI: 10.1007/s11606-010-1571-y
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium Porcinum Peritonitis in a Patient on Continuous Ambulatory Peritoneal Dialysis

Abstract: Mycobacterium porcinum has been reported to cause a variety of illnesses including wound infections, respiratory tract infections, osteomyelitis and catheter-related bacteremias. We report the first case of M. porcinum peritonitis in a patient on continuous ambulatory peritoneal dialysis (CAPD). A 67-year-old woman on CAPD presented with three weeks of constitutional symptoms and abdominal pain. Peritoneal fluid cultures on day three grew acid-fast rods. Nocardiosis was suspected and the patient was empiricall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Wallace et al reported wound infections (62%), central catheter infections and/or bacteremia (16%), and possible pneumonitis (18%) as clinical infections caused by M. porcinum [ 4 ]. In the literature review, we found one case report of M. porcinum infection: peritonitis in continuous ambulatory peritoneal dialysis (CAPD) patients [ 9 ]. NTM are opportunistic pathogens, and factors known to predispose infection are structural lung diseases, like COPD, cystic fibrosis (CF), and prior tuberculosis, with disseminated infection seen in patients with severe immunocompromise, like HIV/AIDS, transplant recipients, hematologic malignancy, and inherited immune syndrome affecting IFN gamma and interleukin 12 and those on immunosuppressive therapy with TNF alpha inhibitors [ 5 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wallace et al reported wound infections (62%), central catheter infections and/or bacteremia (16%), and possible pneumonitis (18%) as clinical infections caused by M. porcinum [ 4 ]. In the literature review, we found one case report of M. porcinum infection: peritonitis in continuous ambulatory peritoneal dialysis (CAPD) patients [ 9 ]. NTM are opportunistic pathogens, and factors known to predispose infection are structural lung diseases, like COPD, cystic fibrosis (CF), and prior tuberculosis, with disseminated infection seen in patients with severe immunocompromise, like HIV/AIDS, transplant recipients, hematologic malignancy, and inherited immune syndrome affecting IFN gamma and interleukin 12 and those on immunosuppressive therapy with TNF alpha inhibitors [ 5 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…M. porcinum has been reported to be sensitive to fluoroquinolones, including ciprofloxacin, levofloxacin, gatifloxacin, and moxifloxacin, and cephalosporin, including cefoxitin, imipenem, amikacin, linezolid, sulfamethoxazole, and clarithromycin [ 4 , 7 , 9 , 18 ]. This is similar to the sensitivity pattern seen in our case except for resistance to clarithromycin.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in an Asian population found that 3% of peritonitis in patients on CAPD was caused by rapid-growing NTM (80% due to M. abscessus) with high rates (80%) of catheter loss and increased three month mortality (40%). 14 Notably, M. porcinum peritonitis has been reported only once, 15 whereas M. senegalense peritonitis is being reported for the first time in the literature. In our study, we have observed a very low prevalence of Mycobacterium avium species.…”
Section: Discussionmentioning
confidence: 99%
“… M. porcinum is known to infect wild and domestic animals ( 8 ) and exhibits a zoonotic potential, being isolated from bovine milk ( 9 ). Accordingly, M. porcinum is an opportunistic pathogen responsible for wound infections ( 10 ), respiratory tract infections ( 11 – 14 ), bacteremia related to blood catheters ( 10 ) and peritonitis complicating dialysis catheter infections ( 15 ), and postoperative infections ( 16 , 17 ).…”
Section: Genome Announcementmentioning
confidence: 99%